(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
The translation of pharmaceutical terminology presents significant challenges due to the specificity, complexity, and cross-disciplinary nature of the field. Achieving equivalence between source and target languages is essential to ensure accurate communication, patient safety, and regulatory compliance. This article examines the types of equivalence in pharmaceutical translation, identifies common problems faced by translators, and proposes strategies to overcome these issues. The study highlights the importance of linguistic precision, subject-matter expertise, and standardization in the translation process.